THE INFLUENCE OF ELECTRONIC SERVICE QUALITY ON SATISFACTION MEDIATED BY TRUST - Septiawati, Silvi (Sekolah tinggi ilmu ekonomi pemuda, 2023)
This study aims to analyze the effect of electronic service quality on satisfaction mediated by trust. This research uses causal quantitative research. The sampling technique in this study used non-probability sampling using the purposive sampling method. The population in this study includes consumers who have made purchases on online shopping sites in the Surakarta residency area. In this study, there were 96 respondents. The data collection method is by distributing questionnaires and processing using Smart PLS version 4.0. The data analysis used is the outer model, namely convergent validity, discriminant validity, composite reliability, cronbach’s alpha, multicollinearity test, and the inner model, namely the coefficient of determination, compatibility, and hypothesis testing. The results of this study indicate that the quality of electronic services has a positive and significant effect on satisfaction mediated by trust.